Allergy and idiopathic generalized epilepsy: A case-control study - Asadi-Pooya, Ali Akbar; Ghetmiri, Ehsan (Journal of Pediatric Neurology, 2007)
The aim of this case-control study was to determine whether there is any association between idiopathic generalized epilepsy and allergic disorders in children. All children with idiopathic epilepsy attending the Motahary Clinic, Shiraz, Iran, in a 7-month period were included in the study. Neurologically normal children, matched for age and sex, were considered as controls. The required data including age, gender, history of allergic disorders, history of smoking in the family members and breast versus formula feeding in the first six months of life were collected. The total number of participants was 110 patients and 100 controls. History of allergic disorders was positive in 28.2% of the patients and 36% of the controls (P = 0.225). When only patients with idiopathic generalized epilepsy were considered (100 patients), allergic disorders were reported in 28%. The prevalence of allergic disorders in patients with idiopathic generalized epilepsy was not significantly different from that in controls (P = 0.225). Family history of allergic disorders was positive in 34.5% of the patients and 45% of the controls (P = 0.122). Our study failed to demonstrate any association or link between idiopathic generalized epilepsy and allergy.
Keywords: Allergy; epilepsy; children